PEMIMPIN NON-MUSLIM DALAM WACANA TAFSIR: Studi Komparatif Tafsir Al-Misbah dan Ibnu Katsir - Mahmudah, Zohratul; Tarmizi Tahir, Muhammad (Jurnal AlifLam Journal of Islamic Studies and Humanities, 2021)
This study discusses non-Muslim leadership which is a problematic issue in the context of relations between religious communities in Indonesia, especially for Muslims in carrying out socio-political-religious relations with non-Muslims. The problematic issue of non-Muslim leadership lies in the state constitution which allows it but the religious constitution (based on the textuality of the Qur'an) prohibits it. This study focuses on two problems, first, how is the interpretation of surah al-Maidah verse 51 on non-Muslim leadership? Second, how is the interpretation of surah al-maidah verse 51 in the context of Indonesia (M. Quraish Shihab) and the Middle East (Ibn Katsir)?. This research is a library research using the maudu'i (thematic) method, with a descriptive analysis approach, namely by describing or outlining the interpretations and opinions of the mufassirs about non-Muslim leadership in surah al-maidah verse 51, then the data collected obtained will be analyzed. Based on the research above, this research can be concluded that; M. Quraish Shihab in interpreting the verse (prohibition) of non-Muslim leadership (QS. Al-Ma'idah: 51) is contextual, or in other words the verse is understood as sociological and not theological. Therefore he allowed the leadership of non-Muslims. In contrast to Ibn Kathir because his approach is more inclined to use language and history, he is more textual.